Tác động của chuyển đổi số đến tăng trưởng kinh tế tại các quốc gia châu Á - Huỳnh Thị Tuyết Ngân; Nguyễn Ngọc , Tân; Phạm Hải , Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The rapid development of digital technologies over the last decade has changed the way governments, businesses, and people in countries all over the world interact with one another. Evidence shows that digital transformation has a positive impact on economic growth. This research was carried out to assess the impact of digital transformation on economic growth and find solutions to the phenomenon of "leapfrogging" in developing and emerging economies. The results found that digital transformation positively impacted economic growth in Asian countries by estimating SGMM with data from 30 Asian countries from 2004 to 2019. At the same time, the study’s findings indicate that it is difficult for developing and emerging economies to use digital transformation to "leapfrogging" in promoting economic growth.